2019
DOI: 10.1093/ofid/ofz257
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proinflammatory Cytokines Are Markers of Disease Severity and Bacterial Burden in Pulmonary Tuberculosis

Abstract: Background Type 1, type 17, and other proinflammatory cytokines are important in host immunity to tuberculosis (TB) in animal models. However, their role in human immunity to TB is not completely understood. Methods To examine the association of proinflammatory cytokines with pulmonary TB (PTB), we examined the plasma levels of type 1 (interferon [IFN]γ and tumor necrosis factor [TNF]α), type 17 (interleukin [IL]-17A and IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 31 publications
13
67
1
1
Order By: Relevance
“…We found that EPA/DHA therapy lowered the pro-inflammatory plasma cytokines IL-1β and TNF-α as well as lung IL-1α and IFN-γ. This is in congruence with the lower bacterial load [45] and a more pro-resolving lung LM profile found in the EPA/DHA group, resulting from changes in the FA composition evident in all FA pools measured. In contrast to these findings, iron supplementation resulted in a higher n-6 LCPUFA composition of PBMCs and lung tissue membranes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that EPA/DHA therapy lowered the pro-inflammatory plasma cytokines IL-1β and TNF-α as well as lung IL-1α and IFN-γ. This is in congruence with the lower bacterial load [45] and a more pro-resolving lung LM profile found in the EPA/DHA group, resulting from changes in the FA composition evident in all FA pools measured. In contrast to these findings, iron supplementation resulted in a higher n-6 LCPUFA composition of PBMCs and lung tissue membranes.…”
Section: Discussionsupporting
confidence: 83%
“…Improvements in inflammation mediated the improvements in the biomarkers of iron status and anemia of infection in the EPA/DHA and Fe groups. Mutually, TNF-α, IFN-γ, and IL-1 are important in host defense against TB, but higher concentrations of these markers have also been associated with worsened lung pathology together with disease severity [43][44][45]. We found that EPA/DHA therapy lowered the pro-inflammatory plasma cytokines IL-1β and TNF-α as well as lung IL-1α and IFN-γ.…”
Section: Discussionmentioning
confidence: 62%
“…High concentrations of cytokines and chemokines were required for early protection against Mtb infections [13]. Plasma cytokines also could be biomarkers of disease severity, and relieve mycobacterial burden in PTB [14]. Our results consistent with report that PTB individuals displayed significantly elevated levels of CCL1, CCL3, CXCL1, CXCL10 and CXCL11 as bacterial burdens dependent.…”
Section: Discussionsupporting
confidence: 90%
“…Our results consistent with report that PTB individuals displayed significantly elevated levels of CCL1, CCL3, CXCL1, CXCL10 and CXCL11 as bacterial burdens dependent. The chemokines were significantly reduced following successful treatment [14].…”
Section: Discussionmentioning
confidence: 97%
“…88,89 In contrast, boosting TH cytokine responses could serve as a feasible strategy for those with acute/recent Mtb infection. 90,91 Cytokines may polarize the immune response in favour of host protection by strengthening immune and memory responses or by disrupting and penetrating the granuloma to expose Mtb bacilli to anti-TB treatment (Table 2; Fig. 1).…”
Section: Vitamins and Biologicsmentioning
confidence: 99%